EMPLOYEE REACTIONS TO CROSS-BORDER ACQUISITIONS: EVIDENCE FROM AN ACQUIRED SERBIAN COMPANY - Savović, Slađana (Economic Annals, 2021)
The purpose of this paper is to examine factors influencing employee re-actions to changes brought about by cross-border acquisitions. The research was con-ducted in a company operating in Serbia’s retail sector that was acquired by a Belgian multinational company. The data were col-lected from 344 respondents. Measures of central tendency, the Mann-Whitney U test, and regression analysis were used to test the research hypotheses. The research results show that employee reactions to changes brought by cross-border acquisi-tion were generally positive. The study show that corporate cultural differences between the acquiring company and the acquired company and the support of transforma-tional leaders resulted in employees react-ing positively to the changes. The study attempts to improve understanding of employee reactions during the process of change occurring as a result of cross-border acquisition. Additionally, this study has practical implications, as it points to how the appropriate management of human resources contributes to positive employee reactions.